Sulfonylated Indeno[1,2-c]quinoline Derivatives as Potent EGFR Tyrosine Kinase Inhibitors - Kowit Hengphasatporn; Thitinan Aiebchun; Panupong Mahalapbutr; Atima Auepattanapong; Onnicha Khaikate; Kiattawee Choowongkomon; Chutima Kuhakarn; Jatuporn Meesin; Yasuteru Shigeta; Thanyada Rungrotmongkol (ACS Omega, 2023)
of ∼20 nM). In a cell-based assay in human cancer cell lines with EGFR overexpression (A549 and A431 cells), the eight selected SIQs all showed more significant cytotoxicity against A431 than A549 cells, consistent with the higher EGFR expression in A431 cells. Molecular docking and FMO-RIMP2/PCM calculations revealed that SIQ17 occupies the ATP-binding site of EGFR-TK, where its sulfonyl group is mainly stabilized by C797, L718, and E762 residues. Triplicate 500 ns molecular dynamics (MD) simulations also confirmed the binding strength of SIQ17 in complex with EGFR. Overall, the potent SIQ compounds obtained in this work could be further optimized for developing novel anticancer drug candidates targeting EGFR-TK.
Keywords: Quinazolinone synthesis and applications; Synthesis and biological activity; Synthesis and Catalytic Reactions